Friction-induced interbank rate volatility under alternative interest corridor systems - Thomas Link; Ulrike Neyer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper proposes rules for the control of interbank rate volatility under different interest corridor systems when volatility stems from interbank market frictions. Friction-induced volatility will occur if there is heterogeneity in two dimensions (across banks and time) with respect to the degree to which frictions change the relative attractiveness of banks' outside options to using the interbank market. Under a "floor" or "ceiling operating system" (asymmetric scheme), friction-induced volatility can be controlled by implementing a relatively wide interest corridor - which is the inversion of the traditional principle. Under a "standard corridor system" (symmetric scheme), the systematic control of friction-induced interbank rate volatility can never be achieved through corridor width adjustments but requires a switch to an asymmetric corridor scheme.
Keywords: E52; E58; G21; 330; interbank market; monetary policy implementation; interest corridor; floor operating system; transaction costs; excess reserves